Low‐magnitude high‐frequency vibration enhances gene expression related to callus formation, mineralization and remodeling during osteoporotic fracture healing in rats. Issue 12 (17th August 2014) - Chung, Shu‐Lu; Leung, Kwok‐Sui; Cheung, Wing‐Hoi
ABSTRACT Low magnitude high frequency vibration (LMHFV) has been shown to improve anabolic and osteogenic responses in osteoporotic intact bones and during osteoporotic fracture healing; however, the molecular response of LMHFV during osteoporotic fracture healing has not been investigated. It was hypothesized that LMHFV could enhance osteoporotic fracture healing by regulating the expression of genes related to chondrogenesis (Col‐2), osteogenesis (Col‐1) and remodeling (receptor activator for nuclear factor‐ κ B ligand (RANKL) and osteoproteger (OPG)). In this study, the effects of LMHFV on both osteoporotic and normal bone fracture healing were assessed by endpoint gene expressions, weekly radiographs, and histomorphometry at weeks 2, 4 and 8 post‐treatment. LMHFV enhanced osteoporotic fracture healing by up‐regulating the expression of chondrogenesis‐, osteogenesis‐ and remodeling‐related genes (Col‐2 at week 4 (p = 0.008), Col‐1 at week 2 and 8 (p < 0.001and p = 0.008) and RANKL/OPG at week 8 (p = 0.045)). Osteoporotic bone had a higher response to LMHFV than normal bone and showed significantly better results as reflected by increased expression of Col‐2 and Col‐1 at week 2 (p < 0.001 for all), larger callus width at week 2 (p = 0.001), callus area at week 1 and 5(p < 0.05 for all) and greater relative area of osseous tissue (p = 0.002) at week 8. This study helps to understand how LMHFV regulates gene expression of callus formation, mineralization and remodeling during osteoporotic fracture healing. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1572–1579, 2014.